2020
DOI: 10.4209/aaqr.2020.05.0248
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Influenza and Enterovirus Infection in Taiwan during the COVID-19 Pandemic

Abstract: Coronavirus disease 2019 (COVID-19) caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is believed to be transmitted through respiratory droplets, aerosols, and contact. During the COVID-19 pandemic, Taiwan has implemented timely and accurate non-pharmaceutical intervention (NPI) measures on a national level (i.e., border control, quarantine and isolation, contact tracing, delay of school opening, and suspension of mass gatherings), and promoted personal hygiene habits to the public (i.e., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
1
4
1
Order By: Relevance
“…Our results provide compelling evidence that current NPIs may have limited impacts on combating non‐enveloped NCRVs. Contrary to existing findings from TNIDSS and the National Health Insurance Research Database, our hospital‐based research showed that test positivity rates in both adults and children for EnV/RhV remained stagnant 19 . The observed differentiated impacts of NPIs on enveloped and non‐enveloped viruses can be explained by three factors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results provide compelling evidence that current NPIs may have limited impacts on combating non‐enveloped NCRVs. Contrary to existing findings from TNIDSS and the National Health Insurance Research Database, our hospital‐based research showed that test positivity rates in both adults and children for EnV/RhV remained stagnant 19 . The observed differentiated impacts of NPIs on enveloped and non‐enveloped viruses can be explained by three factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Subjected to such limitations, our test positivity rates of EnV/RhV can be biased and of limited use. Lastly, physical distancing, the universal wearing of masks, and hand hygiene have all been reported to be effective in reducing NCRVs transmission 16‐19 . While non‐pharmaceutical interventions might have had synergistic effects to prevent transmission of NCRVs, the size and extent of effectiveness should be carefully examined through a systemic approach.…”
Section: Discussionmentioning
confidence: 99%
“…We also speculate that the continuous promotion of hygiene and social distancing measures may have played a role. Other studies showed that this pandemic affected the circulation of several viral pathogens particularly in the pediatric population [7][8][9][10][11][12] and results similar to ours were recently published (data from Minnesota, USA). 13 A better understanding of this phenomenon could help to control more effectively epidemic infectious diseases.…”
Section: Covid-19 Pandemic and Its Consequences Disrupt Epidemiology supporting
confidence: 87%
“…While enterovirus infections often present relatively mild symptoms, infections with polio enteroviruses are typically associated with severe complications. Every year in Taiwan, enterovirus infections begin to spread in late March and reach a peak around mid-June [ 3 ]. Therefore, it is crucial to diagnose these viral infections early and establish a surveillance program to monitor them further.…”
Section: Introductionmentioning
confidence: 99%